2014
DOI: 10.1142/s2010139214500189
|View full text |Cite
|
Sign up to set email alerts
|

Information Efficiency and Firm-Specific Return Variation

Abstract: Reasoning that private firm-specific information causes firm-specific return variation that drives down market-model R2s, [Morck et al., 2000, The Information Content of Stock Markets: Why do Emerging Markets have Synchronous Stock Price Movements? Journal of Financial Economics, 58, 215–260] begin a large body of research which interprets R2 as an inverse measure of price informativeness. Low-R2s or "synchronicity," as it is called in this literature, signal that prices more efficiently incorporate private fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(47 citation statements)
references
References 77 publications
9
37
0
1
Order By: Relevance
“…We also find a negative relation between the quality of disclosure and idiosyncratic risk. Our evidence is consistent with the prediction of LeRoy and Porter (1981) and evidence from the United States by Kelly (2007) and Teoh, Yang, and Zhang (2008) that firms with a worse information environment are more volatile, but it is inconsistent with the view in the R 2 literature that better disclosure is associated with higher idiosyncratic risk (see, for example, Jin and Myers (2007)). Though John, Litov, and Yeung (2008) find a positive relation between country‐level cross‐sectional volatility in the ratio of EBITDA (earnings before interest, taxes, depreciation, and amortization) to total assets and a measure of accounting disclosure requiring 5 years of data for each firm, their result is not inconsistent with our evidence because their measure of risk can increase with the volatility of the systematic component in a firm's EBITDA 6…”
supporting
confidence: 70%
“…We also find a negative relation between the quality of disclosure and idiosyncratic risk. Our evidence is consistent with the prediction of LeRoy and Porter (1981) and evidence from the United States by Kelly (2007) and Teoh, Yang, and Zhang (2008) that firms with a worse information environment are more volatile, but it is inconsistent with the view in the R 2 literature that better disclosure is associated with higher idiosyncratic risk (see, for example, Jin and Myers (2007)). Though John, Litov, and Yeung (2008) find a positive relation between country‐level cross‐sectional volatility in the ratio of EBITDA (earnings before interest, taxes, depreciation, and amortization) to total assets and a measure of accounting disclosure requiring 5 years of data for each firm, their result is not inconsistent with our evidence because their measure of risk can increase with the volatility of the systematic component in a firm's EBITDA 6…”
supporting
confidence: 70%
“…One group of works argues that greater idiosyncratic volatility implies greater price informativeness (Morck et al., ; Durnev et al., ; and Jin and Myers, ). A second stream of studies contends that greater idiosyncratic volatility indicates a poorer information environment (West, ; Krishnaswami and Subramaniam, ; Brown and Kapadia, ; and Dasgupta et al., ); consistent with this view, it has been suggested that idiosyncratic volatility reflects noise trading (Roll, ; and Kelly, ) or limits to arbitrage (Pontiff, ; Wurgler and Zhuravskaya, ; and Mashruwala et al., ). Lee and Liu () try to reconcile the different views on idiosyncratic volatility and price informativeness; they develop a model showing that idiosyncratic volatility has either a U‐shaped or negative relation with price informativeness; using six widely used price informativeness measures, they also document a U‐shaped relation between idiosyncratic volatility and price informativeness.…”
mentioning
confidence: 99%
“…Taken together, the studies discussed above suggest that a higher R 2 implies a higher level of firm opacity. However, this view has been challenged by recent studies (Dasgupta et al., ; Chan et al., ; Kelly, ) that have argued the opposite—that a higher level of R 2 is associated with greater transparency rather than opacity. The number of analysts who follow a company is frequently used as a measure of information that is available about a firm.…”
Section: Measures Of Firm Opacitymentioning
confidence: 99%
“…This line of argument suggests that higher R 2 implies higher firm opacity. However, Kelly () finds that low R 2 stocks appear to have the greatest degree of information asymmetry compared to their high R 2 counterparts. Similarly, Dasgupta, Gan, and Gao () show that stock return synchronicity is significantly higher for older (arguably less opaque) firms.…”
mentioning
confidence: 99%